2020
DOI: 10.1371/journal.pone.0233702
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatic stellate cell activation-related genes in HBV-, HCV-, and nonalcoholic fatty liver disease-associated fibrosis

Abstract: Liver fibrosis is a manifestation of chronic liver injury. It leads to hepatic dysfunction and is a critical element in the pathogenesis of cirrhosis and hepatocellular carcinoma. The activation of hepatic stellate cells (HSC) plays a central role in liver fibrogenesis of different etiologies. To elucidate the molecular mechanism of this phenomenon, it is important to analyze the changes in gene expression that accompany the HSC activation process. In this study, we isolated quiescent and activated HSCs from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…In another example, we linked an NP-enhancer hotspot to tyrosine kinase SYK , the hepatic expression of which positively correlates with fibrosis stage in human tissues(85). NP-specific enhancer associated genes that were previously reported in cell/animal models but reported in our study for the first time in humans include: ARID5B (hepatic stellate cell activation(86)), ARRB2 (fibrosis(87)), FMNL1 (macrophage migration(88)), and PANX1 (apoptosis and fibrosis(8991)). We also uncovered novel genes that had not been previously linked to NASH progression in humans or animal models.…”
Section: Discussionsupporting
confidence: 53%
“…In another example, we linked an NP-enhancer hotspot to tyrosine kinase SYK , the hepatic expression of which positively correlates with fibrosis stage in human tissues(85). NP-specific enhancer associated genes that were previously reported in cell/animal models but reported in our study for the first time in humans include: ARID5B (hepatic stellate cell activation(86)), ARRB2 (fibrosis(87)), FMNL1 (macrophage migration(88)), and PANX1 (apoptosis and fibrosis(8991)). We also uncovered novel genes that had not been previously linked to NASH progression in humans or animal models.…”
Section: Discussionsupporting
confidence: 53%
“…In a preceding study, SOX4 upregulation was suggested to be associated with the progression of IPF [ 38 ]. Known as a fibrogenic gene, SOX4 potentially contributes to activation of hepatic stellate cells and promotion of PF pathology [ 39 ]. Furthermore, the interaction between miR-186 and SOX4 and their functional mechanisms in IPF have been addressed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study has indicated that SOX9 could promote HSCs activation and exacerbate liver fibrosis [ 28 ]. Nevertheless, the mechanism how SOX9 regulates HSCs activation and fibrotic liver remains unclear.…”
Section: Resultsmentioning
confidence: 99%